THE USE OF FELDMAN'S METHOD AS SELF CRITIC IN THE PROCESS OF ART CREATION - Erika Ernawan; Nathalia Yunita Sugiharto (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research investigates the impact of social media on young artists' self-image and creative process within a studio practice context, exploring how digital influences shape their visual identities and thematic choices. Through Feldman’s art criticism model comprising description, analysis, interpretation, and judgment, this study provides a structured critique of students’ artworks. It examines how social media aesthetics guide their artistic decisions and influence their conceptual frameworks. The study uses qualitative methods, including interviews, observations, visual analyses, and documentation, to capture primary data on the interaction between digital media and creative expression. Findings reveal that social media informs students’ stylistic choices and prompts critical reflection on external influences affecting their artistic practice. Feldman’s framework aids students in critically analyzing existing works, enhancing their observational skills, and strengthening their contextual and conceptual thinking during the initial stages of creation. This approach offers a valuable alternative pedagogical method for painting courses in art universities, encouraging students to engage analytically with digital aesthetics in their creative development.